Understanding vulnerabilities in cyber physical production systems. Issue 6 (3rd June 2022) - Khalid, Azfar; Khan, Zeashan Hameed; Idrees, Muhammad; Kirisci, Pierre; Ghrairi, Zied; Thoben, Klaus-Dieter; Pannek, Jürgen
ABSTRACT: Development of future manufacturing systems is featured with flexibility, mass customization, intelligence and context based learning to produce smart products. These production systems are characterized through networked, cooperating objects called cyber physical systems (CPSs). From the manufacturing perspective, the ability to communicate data and develop interaction between devices, manufacturing machinery, raw materials, working robots, humans and the plant environment develops the concept of cyber physical production systems (CPPS). Human-robot collaboration is a technology area that will be an integrated part of the future factory floor and the CPPS. With the involvement of human part in the automated system industrial scenarios, practical safety issues are expected to arise in the connected environment due to the use of a large number of devices, sensors, and cloud services causing complex network, IP conflicts, compromised nodes and communication issues. This all may lead to occupational safety issues on the factory floor in different ways and combinations. Overall, the system's physical vulnerability will be increased in the context of compromised connected working space and cyber-security. In this paper, the authors developed a risk assessment based on system vulnerability of a CPPS developed for a use case requirement and performed a simulated approach by launching a cyber-attack and measuring the causal effect to identify implications on human worker safety.